Revealing the specific status of Mellicta distans Higgins, 1955, stat. n. (Lepidoptera, Nymphalidae) with morphological and molecular characters - Kovalenko, Margarita G.; Kolesnichenko, Kirill A.; Kudryavtseva, Anna A. (Zootaxa, 2020)
A detailed comparison of the taxa Mellicta aurelia distans Higgins, 1955, M. aurelia aurelia (Nickerl, 1850), and M. alatauica (Staudinger, 1881) was performed. The geographic isolation of M. aurelia distans, its habitat preferences, as well as clear differences in the female and male genitalia compared with M. aurelia aurelia, indicate that the taxon distans is an independent species. Molecular data based on sequencing of cytochrome oxidase subunit I (COI) of the mitochondrial DNA confirmed our morphological results. Both the morphological and the molecular results showed a high degree of divergence of M. alatauica from the related species.